Pemahaman Konsep Logaritma Siswa SMA Ditinjau dari Kemampuan Matematika - Yanuar Hery Murtianto; Muhtarom Muhtarom; Eka Devi Setiyaningrum (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
This Understanding the concept is the ability of students to understand a mathematical meaning both in theory and its application in solving problems based on the formation of their own knowledge, not just memorizing. The purpose of this study was to analyze the understanding of students' concepts in the material logarithm class x in terms of mathematical abilities. This research is descriptive qualitative research conducted at SMK N 5 Semarang, with research subjects in class X TP 1. To be able to know the understanding of concepts in students it is done by giving a test that includes seven indicators of mathematical abilities namely understanding, solving problems, connections, communication, reasoning, critical thinking, and creative thinking. The stages carried out consisted of three phases, namely: giving a test of mathematical ability, giving a concept understanding test, and interviewing. From the results of the study using triangulation methods, namely by comparing the results of tests of mathematical understanding in writing with the interview test. The results of qualitative analysis show that: (1) students with TKA mathematical abilities can understand the concept by defining logarithms using writing and symbols, can mention and apply logarithmic properties, can transform logarization forms into exponent forms, can compare examples and not logarithmic examples. (2) students with mathematical skills TKC mathematical abilities can understand the concept by defining logarithms with writing and symbols, changing the shape of logarithms to exponent forms, can only apply logarithmic properties to addition and subtraction, can only compare examples and not just 2. logarithms. (4) students with TKE mathematical abilities can understand the concept by defining logarithms using symbols, can only apply the logarithmic properties of addition and subtraction but cannot specify the properties, can only mention examples and not examples of logarithms 1.